B434 The role of erector spinae plane block in the post-open abdominal surgery care of a paediatric vacterl patient. (11th August 2022) - Pereira, AP; Dias, AL; Félix, AF; Pires, MA
Abstract : Background and Aims: VACTERL syndrome is an acronym for congenital vertebral, anal, cardiovascular, tracheo-esophageal, renal and limb defects (at least three needed for diagnosis). Anaesthetic care can be challenging. The erector spinae plane block (ESPB) can provide abdominal somatic and visceral analgesia. We describe its successful use to provide effective postoperative analgesia and circumvent limitations after open supraumbilical abdominal surgery in a poorly developed infant. Methods: A 5-months-old, 4kg, with VACTERL, presents for Nissen fundoplication and gastrostomy. During her 180-day hospital stay she underwent primary esophageal atresia repair, colostomy, tracheostomy, had multiple respiratory complications, three mechanical ventilation cycles, and received long-term opioid therapy showing withdrawal symptoms after discontinuation. After anaesthesia induction, surgery started laparoscopically but due to patient's intolerance to pneumoperitoneum was converted to a midline laparotomy. Intraoperatively, IV fentanyl 10mcg, paracetamol 60mg and morphine 0, 2mg were administered. Endmost, ultrasound-guided bilateral T7-T8 single shot ESPB (3+3 ml ropivacaine 0, 15%) was performed. For postoperative pain management we elected IV paracetamol 60mg 6/6h and rescue morphine. Results: Patient was extubated uneventfully. Based on comfort level, stable vital signs, limited oxygen requirement and absent need for rescue medication, she was safely discharged to the ward, obviating the need for ICU. FLACC score was used to assess pain at 0–3-6–18 hours and was 0–3/10 over time. No rescue opioid was administered. Parents were satisfied and no postoperative complications were observed. Conclusions: ESPB appears to be useful for pain management purposes in upper abdominal surgeries in pediatric patients with pulmonary impairment and pain treatment concerns, with optimal safety profile and sensitive coverage.